Development of the Bystander and Islamic Values (BIV) Scale to Measure Anti-Bullying Behavior for Junior High School Students - Dani Cahyani; Alfita Choirun Amalia; Kusaeri; Suparto (Nadwa: Jurnal Pendidikan Islam, 2026)
The BIV Scale is a psychometric instrument designed to measure anti-bullying bystander behavior by integrating Islamic Religious Education (IRE) values into a standardized measurement framework. Unlike existing bystander behavior instruments developed primarily within secular Western contexts, the BIV Scale operationalizes the Islamic psychospiritual constructs of murāqabah, ta'āwun, and 'adālah as measurable behavioral dimensions. This study aimed to develop and validate the instrument for use among junior high school and Islamic junior high school students. A psychometric instrument development design was employed, incorporating content validity, exploratory and confirmatory factor analyses, and reliability testing. Data were obtained from expert validators and 200 students. The findings demonstrated excellent content validity (mean Aiken's V = 0.903), identified a theoretically consistent four-factor structure, confirmed an excellent model fit through confirmatory factor analysis, and showed satisfactory internal consistency across all dimensions (McDonald's Omega = 0.798–0.850). These findings confirm that the BIV Scale is a valid and reliable instrument for assessing anti-bullying bystander behavior grounded in Islamic Religious Education values. The instrument contributes to culturally responsive educational measurement and provides a robust framework for evaluating anti-bullying behavior in Muslim educational contexts.